Enhancing Elementary School Students’ Civic Literacy through Inquiry-Based Learning Strategies: A Quasi-Experimental Study in Indonesia - Rahman, Dian Anugrah; Adlina, Fadiah (Yayasan Zia Salsabila, 2023)
This study investigates the effectiveness of inquiry-based learning strategies in enhancing civic literacy among elementary school students in Kendari, Indonesia. Civic literacy—which encompasses understanding of rights, responsibilities, and democratic values—is crucial for shaping active and responsible citizens. The objective of this research is to evaluate the impact of inquiry-based instruction on students’ cognitive and affective capacities in understanding civic concepts. A quasi-experimental design was employed, utilizing a pre-test and post-test approach with 60 elementary students as participants. Data were collected through observations, interviews, and focus group discussions, and analyzed using NVivo software to identify emerging themes. The findings indicate a significant improvement in students’ civic literacy, including a deeper comprehension of basic civic concepts, enhanced critical thinking skills, and more positive attitudes toward democracy and social justice. These results underscore the importance of implementing inquiry-based learning as an effective pedagogical approach to improve the quality of civic education. The study offers practical implications for curriculum development and teacher training programs to foster the effective use of inquiry strategies in classrooms.